Does team psychological capital moderate the relationship between authentic leadership and negative outcomes: an investigation in the hospitality industry. Issue 1 (1st January 2018) - Megeirhi, Huda A.; Kilic, Hasan; Avci, Turgay; Afsar, Bilal; Abubakar, A. Mohammed
Abstract: The recent theoretical advances in positive organisational variables like authentic leadership and collective psychological capital (PsyCap) provide the credo to test the possible moderating effect of collective psychological capital in the form of team PsyCap. The purpose of this study is to test a model linking authentic leadership with employee cynicism, tolerance to workplace incivility and job search behaviour at the group level. A sample of 331 employees (45 teams) from the hospitality industry in the Arab Middle Eastern context was utilised (Jordan). The findings indicated that authentic leadership was significantly related to the aforementioned variables; and team psychological capital moderated the relationship between authentic leadership and tolerance to workplace incivility. Implications for practice and theory are discussed.